Pengaruh Perlakuan Asam Hidrofluorat terhadap Kandungan SiO₂ dan Al₂O₃ dalam Red Mud untuk Meningkatkan Kadar Fe₂O₃ - Nafisah, Sayyidatun; Hidayat, Arif; Khaerudini, Deni Shidqi (Chemistry Department, Universitas Islam Indonesia, 2025)
Red mud is a solid waste generated from the Bayer process that contains valuable metals such as Fe₂O₃, Al₂O₃, SiO₂, and TiO₂. However, to optimize red mud as an iron source, the high content of silica and alumina must be reduced, as these impurities can lower the efficiency of iron processing. This study aims to evaluate the leaching of red mud using 100 mL of 6.5 M hydrofluoric acid (HF), with variations in red mud mass (10, 20, 25 g) and stirring time (1 to 6 hours), to produce iron-rich residue. XRF analysis showed an increase in Fe₂O₃ content up to 44.65% in the 25 g sample after 6 hours. Al₂O₃ content consistently decreased, while SiO₂ decreased to 20.23% after 4 hours. XRD results revealed that the dominant phases in the residue were hematite, magnetite, and goethite, while silica and alumina phases were diminished. The optimal condition was achieved with 25 g of red mud and 4 hours of reaction time, resulting in high Fe₂O₃ content and low impurities. ICP-MS analysis of the leachate showed increasing Si and Al concentrations with longer reaction times, indicating HF selectively dissolved both elements. The novelty of this research lies in the use of HF to selectively dissolve Si and Al without affecting iron, yielding a residue with potential use as a precursor for magnetite or other iron-based materials. This method effectively reduces impurities and enhances residue quality, supporting sustainable red mud processing and circular economy initiatives.